Simultaneous Calibration of Multiple Microphones for Both Phase and Amplitude in an Impedance Tube - Péter TÓTH; Christophe SCHRAM (Archives of Acoustics)
This paper presents and compares microphone calibration methods for the simultaneous calibration of small electret microphones in a wave guide. The microphones are simultaneously calibrated to a reference microphone both in amplitude and phase. The calibration procedure is formulated on the basis of the damped plane wave propagation equation, from which the acoustics field along the wave guide is predicted, using several reference measurements. Different calibration models are presented and the methods were found to be sensitive to the formulation, as well as to the number of free parameters used during the reconstruction of the wave-field. The wave guide model based on five free parameters was found to be the preferred method for this type of calibration procedure.